Relations of Household Socio-Economic Condition with the Interest of Rural Youth in Agricultural Sector - Melia Sari; Endriatmo Soetarto; Muhammad Shohibuddin (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2017)
Agricultural activities work must be able to fulfill the economic needs and approved by the community as a decent job, so many people enthusiast. Nowadays, interested of youth from the family farmers is decreasing to work in agriculture. It shows from the socio-economic conditions of farm households. The purpose of this study is to analyze the relationship of land ownership, income, housing conditions and education to the interests of village youth in agriculture. This research uses quantitative data approach with survey method supported by qualitative data in the form of in-depth interview. Respondents consist of 54 youths of children of farmers and aged 16-30 years. The respondents selected by random sampling method. The results of this study indicate that there is a significant relationship between income and housing conditions with the interests of village youth in agriculture.Keywords: agricultural, youth interest, socio-economic conditions================================================ABSTRAKPekerjaan di bidang pertanian harus mampu memenuhi kebutuhan ekonomi dan diakui oleh masyarakat sebagai pekerjaan yang layak sehingga banyak peminatnya. Saat ini minat pemuda desa untuk dapat bekerja di bidang pertanian semakin berkurang. Hal ini dapat dilihat dari keadaan kondisi-sosial ekonomi rumah tangga petani. Tujuan dari penelitian ini adalah untuk menganalisis hubungan kepemilikan lahan, pendapatan, status-kondisi rumah tempat tinggal dan pendidikan dengan minat pemuda desa di bidang pertanian. Penelitian ini menggunakan pendekatan data kuantitatif dengan metode survei yang didukung data kualitatif berupa wawancara mendalam. Responden terdiri dari 54 orang pemuda yang merupakan anak dari petani dan berumur 16-30 tahun. Pemilahan responden melalui metode pengambilan sampel acak. Hasil penelitian ini menunjukkan bahwa terdapat hubungan yang signifikan antara pendapatan dan status-kondisi rumah tempat tinggal dengan minat pemuda desa di bidang pertanian.Kata kunci: pertanian, minat pemuda, kondisi sosial-ekonomi